2018
DOI: 10.1002/hpm.2541
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of effort‐reward imbalance among health workers

Abstract: The purpose of this article is to systematically collate effort-reward imbalance (ERI) rates among health workers internationally and to assess gender differences. The effort-reward (ER) ratio ranges quite widely from 0.47 up to 1.32 and the ERI rate from 3.5% to 80.7%. Many studies suggested that health workers contribute more than they are rewarded, especially in Japan, Vietnam, Greece, and Germany-with ERI rates of 57.1%, 32.3%, 80.7%, and 22.8% to 27.6%, respectively. Institutions can utilize systems such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…There was a correlation between gender and the occurrence of ERI [26]. Our study showed that male ED nurses were more likely to experience ERI than the female nurses, which might be because male nurses often undertook more work in clinical practice [27].…”
Section: Discussionmentioning
confidence: 60%
“…There was a correlation between gender and the occurrence of ERI [26]. Our study showed that male ED nurses were more likely to experience ERI than the female nurses, which might be because male nurses often undertook more work in clinical practice [27].…”
Section: Discussionmentioning
confidence: 60%
“…Occupational stress was measured using Siegrist's effort/reward imbalance (ERI) model, which has been extensively used in HCWs [29][30][31]. The short form [32], Italian version [33], of the ERI questionnaire [34] is composed of 10 questions ranging on a 4-point Likert scale from "strongly disagree" to "strongly agree".…”
Section: Questionnairementioning
confidence: 99%
“…Die Aussagekraft des Gratifikationskrisenmodells wird in ver schiedenen Arbeiten erkennbar: Nguyen et al [8] beschreiben in einem systematischen Review die Heterogenität des Auftretens von Gratifikationskrisen bei Mitarbeitern in verschiedenen Gesund heitssystemen. Die Bedeutung von Stress in Notaufnahmen für die Entstehung von Gratifikationskrisen ist in einigen Studien belegt [9].…”
Section: Introductionunclassified